2006
DOI: 10.1038/sj.bjc.6603412
|View full text |Cite
|
Sign up to set email alerts
|

18FDG uptake during induction chemoradiation for oesophageal cancer fails to predict histomorphological tumour response

Abstract: To determine whether [18 F]-fluorodeoxyglucose-positron emission tomography (FDG-PET) could predict the pathological response in oesophageal cancer after only the first week of neoadjuvant chemoradiation. Thirty-two patients with localised oesophageal cancer had a pretreatment PET scan and a repeat after the first week of chemoradiation. The change in mean maximum standardised uptake value (SUV) and volume of metabolically active tissue (MTV) was compared with the tumour regression grade (TRG) in the final his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 32 publications
(36 reference statements)
2
58
0
4
Order By: Relevance
“…Despite intensive efforts to identify molecular markers, which are predictive for tumour response and prognosis, the value of each of these markers is currently not sufficiently validated to use them for the selection of patients for therapy [43][44][45]. Most previously reported studies showed that changes in tumour glucose uptake assessed by 18 F-FDG PET during or immediately after neoadjuvant therapy were associated with response and prognosis in oesophageal and oesophagogastric cancer [15,21,25,35,37,42,[46][47][48][49][50]. Therefore, a meta-analysis is useful because it reduces the effect that chance plays on the individual result, and quality assessments are important for reducing bias.…”
Section: Discussionmentioning
confidence: 99%
“…Despite intensive efforts to identify molecular markers, which are predictive for tumour response and prognosis, the value of each of these markers is currently not sufficiently validated to use them for the selection of patients for therapy [43][44][45]. Most previously reported studies showed that changes in tumour glucose uptake assessed by 18 F-FDG PET during or immediately after neoadjuvant therapy were associated with response and prognosis in oesophageal and oesophagogastric cancer [15,21,25,35,37,42,[46][47][48][49][50]. Therefore, a meta-analysis is useful because it reduces the effect that chance plays on the individual result, and quality assessments are important for reducing bias.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies [3,[29][30][31][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] have based or part based PET responses according to pathological criteria for determining response, either using reported pathological scoring systems [22,23] or with modifications to these systems. The…”
Section: Predicting Pathological Responsementioning
confidence: 99%
“…Choi NC et al found an inverse correlation between postradiation SUVmax and pathologic tumor response in lung cancer (Choi et al, 2002). Although postradiation SUVmax could be used to stratify the prognosis, it was obviously influenced by radiation inflammatory reaction in prediction survival time (Gillham et al, 2006;Javeri et al, 2009a;Jingu et al, 2010;Suzuki et al, 2011). Most important was that above two parameters did not correlate to survival time (Table 4).…”
Section: Discussionmentioning
confidence: 99%